PENGARUH KUALITAS KEHIDUPAN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PT PERTAMINA PERSERO RU IV CILACAP - Astrianditya Januar Ristanti; Fereshti Nurdiana Dihan (Universitas PGRI Madiun, 2016)
This study titled influence the quality of work life and job satisfaction on employee performance of PT Pertamina Persero RU Cilacap. The purpose of this study was to determine the effect on the quality of work life by partial performance, determine the effect of job satisfaction on performance partially, and determine the influence of the quality of work life and job satisfaction simultaneously on employee performance. The independent variable in this study is the quality of work life and job satisfaction, the dependent variable in this study is the performance. The population of this study were 600 permanent employees shift part of PT. Pertamina Persero RU Cilacap. Sampling technique using census sampling methods and techniques Probability Proportionate Random Sampling Strarified totaling 221 employees. Data collection method used was a questionnaire and the data mengalisis using the multiple linear regression analysis.These results indicate that the quality of work life has significant influence but not the performance, job satisfaction has a significant impact on performance, while the quality of work life and job satisfaction has a significant impact on employee performance remains part of PT Pertamina Persero shift RU Cilacap.